The role of self-esteem, social support and cognitive appraisal on coping strategies of stigmatized gay men and lesbians. - Romero, Rama Lo P
This study examined the relationships among factors influencing coping srategies of stigmatized gay men and lesbians namely: self-esteem, social support, and cognitive appraisal. A total of 60 gay men and lesbians aged 16 to 25, from different schools in Iloilo City and Miagao served as respondents of the study., A survey was conducted and four instruments were used to measure the variables. The design of this study was non-experiemntal. To show the relationship among the variables, data were analyzed using Logistic Regression Analysis. Results indicated that stigmatized gay men and lesbians with higher self-esteem and social support tend to handle stigma-related situations using problem-focused coping strategies rather than emotion-focused coping strategies. Furthermore, gay men and lesbians who evaluate stigma-related situations as challenge appraisals tend to use problem-focused coping strategies than emotion-focused coping strategies in dealing with experienced stigmatization.